2018
DOI: 10.21608/jssae.2018.35531
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Agri-Aquaculture and Seed Treatment Techniques on Sugar Beet Crop

Abstract: The current study aimed to investigate the influence of using different sources of irrigation (well "ground water" and agriaquaculture) with some seed treatments techniques on amount of water applied, water use efficiency, yield and economic analysis of sugar beet crop. An experimental was design on split plot with 6 treatments and three replicates, where three seed treatments techniques i.e. control, soaking (24 h) and soaking (72 h). Drip irrigation was used and crops were planted in rows. Data indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…When irrigation sweet sorghum with fish farm waste water, stalk length exceeds by (109.05 and 109.67 cm), as well as stalk diameter exceeds by (0.91 and 1.32 cm) compared with well ground water during the 1 st and 2 nd seasons, respectively. Moursy (2018) indicated that the morphological measurements were highly enhanced by using agri-aquaculture (fish farm waste water) than ground water resource.…”
Section: Stalk Length and Diameter (Cm)mentioning
confidence: 99%
“…When irrigation sweet sorghum with fish farm waste water, stalk length exceeds by (109.05 and 109.67 cm), as well as stalk diameter exceeds by (0.91 and 1.32 cm) compared with well ground water during the 1 st and 2 nd seasons, respectively. Moursy (2018) indicated that the morphological measurements were highly enhanced by using agri-aquaculture (fish farm waste water) than ground water resource.…”
Section: Stalk Length and Diameter (Cm)mentioning
confidence: 99%